1975
DOI: 10.1126/science.1089999
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon: Role in the Hyperglycemia of Diabetes Mellitus

Abstract: Glucagon suppression by somatostatin reduces or abolishes hyperglycemia in dogs made insulin-deficient by somatostatin, alloxan, or total pancreatectomy. This suggests that the development of severe diabetic hyperglycemia requires the presence of glucagon, whether secreted by pancreatic or newly identified gastrointestinal A cells, as well as a lack of insulin. Glucagon suppression could improve therapeutic glucoregulation in diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
100
2
1

Year Published

1977
1977
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(108 citation statements)
references
References 18 publications
5
100
2
1
Order By: Relevance
“…Lack of insulin increases production of the glycemia-increasing hormone glucagon, an effect thought to underlie uncontrolled hy- perglycemia in T1D rodents (26) and humans (37). Pancreatic preproglucagon mRNA and glucagon levels as well as plasma glucagon levels were elevated in T1D-icv-PBS mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Lack of insulin increases production of the glycemia-increasing hormone glucagon, an effect thought to underlie uncontrolled hy- perglycemia in T1D rodents (26) and humans (37). Pancreatic preproglucagon mRNA and glucagon levels as well as plasma glucagon levels were elevated in T1D-icv-PBS mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We had previously shown that hepatic overproduction of glucose, ketones, and other catabolic manifestations of insulin deficiency cannot occur in the absence of hyperglucagonemia (16). To determine if the antidiabetic effects of leptin might be mediated by glucagon suppression, which was suggested by Tuduri et al (17), we compared plasma glucagon in the four groups of diabetic mice.…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that the dosage may have been relatively low. Others (De Vane et al 1974;Dobbs et al 1975) have obtained greater depressions of glucagon concentrations with larger doses in other species. Furthermore, some of the remaining plasma IRG may represent intestinal glucagon.…”
Section: Discussionmentioning
confidence: 99%